Mendelian randomization eradicates the causal relationship between educational attainment, household income, and oropharyngeal cancer - Qi, Li; Bao, Wenzhao; Wang, Sai; Ding, Xiaoxu; Li, Wei (Frontiers in Oncology, 2023)
Background: It was reported that educational attainment and household income are associated with oropharyngeal cancer. However, whether such an association is causal is still unknown. Methods: The Mendelian randomization (MR) design was performed to disentangle their causal relationship. Initially, genetic variants proxied for educational attainment and household income were extracted from the largest genome-wide association studies (GWAS) and two oropharyngeal GWAS datasets were used in the discovery and validation stages separately. A reverse MR analysis was carried out to judge whether oropharyngeal cancer can affect educational attainment and household income. The results from the two stages were combined using the meta-analysis. The heterogeneity and horizontal pleiotropy were appraised using several methods. Results: All selected genetic variants were valid. In the discovery stage, the genetically-elevated years of education might decrease the risk of oropharyngeal cancer (IVW OR = 0.148[0.025, 0.872], p-value = 0.035) while such a result became insignificant in the validation stage (IVW p-value > 0.05). Household income cannot change the risk of oropharyngeal cancer in both stages. The reverse MR suggested oropharyngeal cancer should slightly alter the household income (IVW OR = 1.001[1.000, 1.003], p-value = 0.036) in the discovery set but the result cannot be replicated in the validation stage. The meta-analysis did not find any significant result either. The results were also assessed by sensitivity analyses and there was no heterogeneity or horizontal pleiotropy in the analyses. The statistical powers were all above 80% in the discovery stage. Conclusions: There should be no causal association between educational attainment, household income, and oropharyngeal cancer.